2020
DOI: 10.3390/ijms21155373
|View full text |Cite
|
Sign up to set email alerts
|

Microvesicles in Cancer: Small Size, Large Potential

Abstract: Extracellular vesicles (EV) are secreted by all cell types in a tumor and its microenvironment (TME), playing an essential role in intercellular communication and the establishment of a TME favorable for tumor invasion and metastasis. They encompass a variety of vesicle populations, among them the well-known endosomal-derived small exosomes (Exo), but also larger vesicles (diameter > 100 nm) that are shed directly from the plasma membrane, the so-called microvesicles (MV). Increasing evidence suggests that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 165 publications
(234 reference statements)
4
41
0
Order By: Relevance
“…However, the specific markers of MV are still lacking; it is hard to differentiate the MVs from other subgroups of EVs by proteins markers. Since the results obtained from current studies have shown that MVs can be used as good biomarkers for diseases without excluding the existence of other vesicles, pure MVs seem not to be necessary in clinical analysis [ 56 , 57 , 58 ]. With the large size, ABs can be easily distinguished from smaller vesicles by transmission electron microscopy (TEM), dynamic light scattering (DLS) and nanoparticle tracking analysis (NTA).…”
Section: Recommendations In Characterization Of Evsmentioning
confidence: 99%
“…However, the specific markers of MV are still lacking; it is hard to differentiate the MVs from other subgroups of EVs by proteins markers. Since the results obtained from current studies have shown that MVs can be used as good biomarkers for diseases without excluding the existence of other vesicles, pure MVs seem not to be necessary in clinical analysis [ 56 , 57 , 58 ]. With the large size, ABs can be easily distinguished from smaller vesicles by transmission electron microscopy (TEM), dynamic light scattering (DLS) and nanoparticle tracking analysis (NTA).…”
Section: Recommendations In Characterization Of Evsmentioning
confidence: 99%
“…Cancer cell derived exosomes promote formation of metastases by initiating epithelial-mesenchymal-transition (EMT) within the tumor microenvironment. They will also travel to distant places (even passing the blood brain barrier) via various interstitial fluids in the extracellular space and be selectively taken up and induce transformation of normal cells into malignant cells [40][41][42][43][44].…”
Section: Exosomes and Malignant Cell Proliferationmentioning
confidence: 99%
“…In the context of cancer biology, evidence is rising that tumour cells, including OC cells, secrete EVs that carry a cargo which is typical of the cell of origin, which facilitates the spread of cancer by priming distant areas of the body to be cancer cell-friendly [27][28][29]. In the OC setting, several studies have pointed to the relevance of EVs present in patients' plasma, serum, and ascites.…”
Section: Introductionmentioning
confidence: 99%